Comparison of V Technique and Femoral Arterial Palpation Techniques Accuracy in Identifying the Femoral Vein’s Cannulation Site - Tantri, Aida Rosita; Alatas, Anas; Dharma, Reza Surya (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: The femoral vein cannulation is essential for vascular access and finding it by just relying on the femoral artery pulsation can be challenging in a certain condition. V technique is a new technique to identify the femoral vein’s cannulation site based on topographic anatomy without relying on femoral artery pulsation. AIM: This study was aimed to compare V technique and arterial palpation technique accuracies in identifying the femoral vein’s cannulation site. METHODS: This study was a cross-sectional study on 115 adult patients aged 18–65 years old with body mass index 18–25 kg/m2 who underwent elective surgery in Cipto Mangunkusumo National General Hospital on February-March 2020. After ethical approval and informed consent, the distance of the femoral vein’s cannulation site identified by both techniques with the skin projection of the femoral vein diameter identified by ultrasonography (USG) were compared in all subjects. Accuracy was defined when the femoral vein’s cannulation sites identified by both techniques were within the skin projection of femoral vein diameter identified by USG. Data were collected and analyzed using SPSS ver 20. RESULTS: The accuracy of the V technique in determining the femoral vein’s cannulation site was 93.9%, while the accuration of the femoral artery pulsation technique was 96.5%. Mcnemar analysis showed no difference in both techniques’ accuracy (p = 0.549). There was a statistically significant positive correlation between the distance of the femoral vein cannulation site predicted by both techniques with the skin projection of the femoral vein midpoint (r = 0.548; p < 0.001). CONCLUSION: V technique’s accuracy was not significantly different from the femoral artery pulsation palpation technique’s accuracy in identifying the femoral vein cannulation site.